The vendor and user organizations characteristics for COTS software evaluation and selection - Baharom, Fauziah; Tarawneh, Feras; Yahaya, Jamaiah; Zainol, Azida; Puteh, Nurnasran; Mohd, Haslina; Muhd Darus, Norida; Marzuki @ Matt, Zaharin; Yasin, Azman (2012)
Since the Commercial off-the-shelf (COTS) software become widespread components in the market for building the systems with less time and cost, the COTS evaluation and selection becomes a non-trivial task. There are many models attempted to propose a set of characteristics for evaluating and selecting COTS software.However, these models have concentrated on the functional and quality characteristics of COTS software, leaving other effective characteristics related to vendor (the organization that developed, support, and realized COTS software) and user (the organization that integrated and used COTS software) organizations. Therefore, this paper proposed a set of important characteristics relevant to the vendor and user organizations that play important role to discriminate between COTS alternatives in COTS evaluation and selection process.Most of the related studies have been analyzed and carefully studied in the literature to identify and propose these characteristics together with their attributes and associated metrics.